Increased Cesarean Section Rates during the COVID-19 Pandemic: Looking for Reasons through the Robson Ten Group Classification System - Silva, Cassia Elane Berbel da; Guida, Jose Paulo Siqueira; Costa, Maria Laura (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To compare cesarean section (CS) rates according to the Robson Ten Group Classification System (RTGCS) and its indications in pregnant women admitted for childbirth during the first wave of the coronavirus disease 2019 (COVID-19) pandemic with those of the previous year.Materials and Methods We conducted a cross-sectional study to compare women admitted for childbirth from April to October 2019 (before the pandemic) and from March to September 2020 (during the pandemic). The CSs and their indications were classified on admission according to the RTGCS, and we also collected data on the route of delivery (vaginal or CS). Both periods were compared using the Chi-squared (χ2) test or the Fisher exact test.Results In total, 2,493 women were included, 1,291 in the prepandemic and 1,202 in the pandemic period. There was a a significant increase in the CS rate (from 39.66% to 44.01%; p = 0.028), mostly due to maternal request (from 9.58% to 25.38%; p < 0.01). Overall, groups 5 and 2 contributed the most to the CS rates. The rates decreased among group 1 and increased among group 2 during the pandemic, with no changes in group 10.Conclusion There was an apparent change in the RTGSC comparing both periods, with a significant increase in CS rates, mainly by maternal request, most likely because of changes during the pandemic and uncertainties and fear concerning COVID-19.
Keywords: cesarean section rates; COVID-19; Robson classification